Pelatihan Penghitungan Zakat Maal Barbasis IT (Aplikasi Zakat) Bagi Staff Lembaga Sosial Pesantren Tebuireng Jombang (Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
Zakat is a term for everything that is issued by someone as an obligation to Allah. Then it is handed over to the poor (or those who deserve it). The emergence of Law No. 23 of 2011 concerning the management of zakat was then followed by the emergence of Government Regulation (PP) No. 14/2014 Concerning the Implementation of Law No.23/2011 Concerning Zakat Management as an operational and technical guideline (juknis) for zakat management laws. LSPT is an institution that collects social funds (infaq, zakat, shodaqoh, waqf) which then redistributes these social funds to those in need (especially the eight groups namely the poor, the poor, the amil, converts, riqob, ghorim, fisabilillah, ibnu sabil, who are in under the auspices of the Tebuireng Islamic Boarding School foundation. The lack of zakat funds managed by LSPT and this is due to the lack of knowledge of LSPT staff about zakat, especially zakat maal. Some of the funds received are included in alms that do not require complicated calculations. The Unhasy PKM TEAM provides training in calculating zakat maal either manually or using the zakat calculation application “Zakat Calculator”. The training uses the lecture tutorial method, practice and discussion. The result of this training is the high enthusiasm of the leadership and staff to take part in the training. The training material is very much in line with the needs at LSPT, and those who lastly is the potential and ability of meni participants In short, it is proven by being able to carry out a simulation of paying zakat maal.